Risiko Penggunaan ACEi Terhadap Kejadian Batuk Kering pada Pasien Hipertensi di RSUD Cengkareng dan RSUD Tarakan DKI Jakarta - Halim, Margareth Christina; Andrajati, Retnosari; Supardi, Sudibyo (Jurnal Kefarmasian Indonesia, 2015)
The use of angiotensin converting enzyme inhibitors (ACEi) as an antihypertensive agent can cause side effects such as dry cough. The aim of this study is to evaluate risk of ACEi administration on dry cough incidence with captopril as the standard against lisinopril and ramipril in hypertensive patients at RSUD Cengkareng and RSUD Tarakan Jakarta. The design of this study is prospective cohort. The inclusion criteria were patients who received ACEi as hypertension therapy for ≤ 3 months gathered from outpatient and willing to participate as sample in this study at RSUD Cengkareng and RSUD Tarakan. Subject of this study consist of 54 patients who received captopril and 54 patients received non captopril ACEi, taken by consecutive sampling from January-July 2014. Data was collected using structured interviews and medical record. Dry cough incidence due to ACEi was evaluated using Naranjo Algorithm and analyzed using Chi Square test. Dry cough incidence was found in 19,44% of sample. No significant relationship of age, gender, ethnic, comorbidity, body mass index (BMI), dosage, and duration of use with the dry cough incidence due to the use of ACEi. There is no difference on dry cough incidence between the use of captopril, lisinopril and ramipril.